Philippine Economic Update : Pursuing Inclusive Growth through Sustainable Reconstruction and Job Creation - World Bank (Washington, DC, 2014)
Despite typhoon Yolanda and a string of natural disasters throughout 2013, Philippine economic growth accelerated to 7.2 percent in 2013. Higher growth was underpinned by the robust performance of consumption and services, and supported by the expansion of investments and manufacturing. Like other emerging markets, Philippine financial markets experienced large volatilities as investors responded to the tapering of the United States (U.S.) stimulus program. Monetary and fiscal policy remained supportive of growth. Amid the challenging global environment and the impact of typhoon Yolanda, the Philippines are likely to sustain high growth in the medium-term. Risks to growth include a slower global recovery, financial market volatilities following the tapering of the U.S. stimulus program, potential bubbles in the real estate sector, slower post-typhoon reconstruction, and domestic reform lags. The government responded quickly to the typhoon by rolling out immediate humanitarian aid and preparing the reconstruction assistance on Yolanda (RAY), a strategic plan to guide recovery and reconstruction in the affected areas. The Philippines will also need to prepare more broadly for the increased risk of disasters brought about by climate change. The Philippine economic update provides an update on key economic and social developments, and policies over the past six months. It also presents findings from recent World Bank studies on the Philippines.